The role of the tumor matrix environment in progression of head and neck cancer. Issue 3 (May 2021) - Saint, Angélique; Van Obberghen-Schilling, Ellen
Abstract : Purpose of review: Head and neck squamous cell carcinoma (HNSCC) tissue is composed of multiple cell types embedded in an extracellular matrix (ECM) that actively participates in disease progression, spread and treatment response. In this review, we provide an update of our current knowledge about the ECM landscape of HNSCC, its functions, methods of analysis, and nonimmunological stromal targeting strategies that modify the tumor ECM to improve conventional and emerging therapies. Recent findings: The tumor ECM differs significantly from that of normal tissue in abundance, composition, organization and mechanical properties. In HNSCC, signaling between malignant epithelial cells and stromal cells prompts the upregulation of a set of ECM components that serve as substrates for carcinoma cell migration, modulate the cytokine environment and promote immune evasion in these tumors. Advanced imaging techniques and molecular profiling at the single-cell level have provided valuable insights into our understanding of the tumor ECM and its role in malignancy, and opened new avenues for predictive and potentially actionable biomarker discovery for more effective management of the disease. Summary: ECM components upregulated in HNSCC can impact several cancer hallmarks by sustaining proliferative signaling, promoting angiogenesis, facilitating invasion and metastasis, modulating growth suppressor activity, and suppressing antitumoral immunity. The tumor ECM is also involved in treatment resistance, making it a potential therapeutic target.